2020
DOI: 10.1253/circj.cj-20-0254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Clopidogrel and Prasugrel Associated With <i>CYP2C19</i> Genotypes in Patients Receiving Percutaneous Coronary Intervention in a Japanese Population

Abstract: Background:The association between cytochrome P450 (CYP) 2C19 genotypes and adverse events in patients treated with clopidogrel or prasugrel after percutaneous coronary intervention (PCI) in the Japanese population is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In addition to the clinical factors, the CYP2C19 LOF allele is an important determinant of HPR. In this study, extensive, intermediate, and poor metabolizers were found in 30.4%, 52.7%, and 16.8% of patients, in line with previous reports 31) . The CYP2C19 LOF allele is well known to be associated with a marked decrease in the platelet response to clopidogrel, as also shown in this study, resulting in a significant interpatient variability of platelet reactivity 32) .…”
Section: Impact Of Clinical and Genetic Factors On Hprsupporting
confidence: 93%
“…In addition to the clinical factors, the CYP2C19 LOF allele is an important determinant of HPR. In this study, extensive, intermediate, and poor metabolizers were found in 30.4%, 52.7%, and 16.8% of patients, in line with previous reports 31) . The CYP2C19 LOF allele is well known to be associated with a marked decrease in the platelet response to clopidogrel, as also shown in this study, resulting in a significant interpatient variability of platelet reactivity 32) .…”
Section: Impact Of Clinical and Genetic Factors On Hprsupporting
confidence: 93%
“…Despite assessing several variants, no statistically significant association was observed between SNPs and outcomes among patients receiving prasugrel. Similar findings emerged from a single-center retrospective Japanese study on patients who had PCI [31]. Therefore, unlike clopidogrel, clinical results are unaffected by genetic variations in many candidate genes.…”
Section: Ticagrelor and Prasugrelsupporting
confidence: 70%
“…This study was a retrospective observational study of consecutive patients who underwent PCI and who had their CYP2C19 variants assessed at Shiga University of Medical Science Hospital between September 2014 and August 2021. 15 CYP2C19 variants are determined in routine clinical practice when drugs that could be metabolized by CYP2C19, such as P2Y12-I or proton pump inhibitors, are used. In the present study, patients were regarded as having HBR when they satisfied at least 1 major and/or 2 minor ARC-HBR criteria.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Previous studies have shown that both clopidogrel and prasugrel are expected to be equally effective in preventing thrombotic events in CYP2C19 LOF non-carriers. 3,10, 15 In addition, prasugrel can prevent ischemic events after PCI without being affected by CYP2C19 LOF carrier or noncarrier status. 16 Therefore, we merged these populations (CYP2C19 LOF non-carriers prescribed clopidogrel and CYP2C19 LOF carriers and non-carriers prescribed prasugrel) as the group with retained P2Y12-I action and compared them to the group with decreased P2Y12-I action.…”
Section: Data Source and Study Populationmentioning
confidence: 99%